Electron density analysis of large (molecular and periodic) systems: A parallel implementation. Issue 26 (31st July 2015) - Casassa, Silvia; Erba, Alessandro; Baima, Jacopo; Orlando, Roberto
<x xml:space="preserve">Abstract</x> A parallel implementation is presented of a series of algorithms for the evaluation of several one‐electron properties of large molecular and periodic (of any dimensionality) systems. The electron charge and momentum densities of the system, the electrostatic potential, X‐ray structure factors, directional Compton profiles can be effectively evaluated at low computational cost along with a full topological analysis of the electron charge density (ECD) of the system according to Bader's quantum theory of atoms in molecules. The speedup of the parallelization of the different algorithms is presented. The search of all symmetry‐irreducible critical points of the ECD of the crystallized crambin protein and the evaluation of all the corresponding bond paths, for instance, would require about 32 days if run in serial mode and reduces to less than 2 days when run in parallel mode over 32 processors. © 2015 Wiley Periodicals, Inc.